Land processing in the urban territory of German Federal Republic - Weiß, Erich (Geodesy and Cartography, 2012)
The main aspects of land owning in German Federal Republic (GFR) are presented by pointing out the special importance of this question. The laws of land ownership and the statements of Constitution are analysed. The essence and background of land handling and its planning exploitation system in GFR are described. Important methods of public-legal restruction of land exploitation are presented when a new urge the city’s and structure places of residence improvement and for the needs of state and market. A consideration of approaching personal and other goals, such as changing of lots of land and their borders is given until to reimbursed land confiscation. Multipartite land possessions planning in GFR presents good provisions for solving the arising controversials in the urbanised territory, especially, in the near-urban places. It helps for avoiding errors of planning and investment. A choice of means of land processing must be regulated to such extent that the state institutions could not act on themselves. The right land accounting facilitates the effective application of land processing means. Article in German. Bodenordnung in städtischen verdichtungsgebieten der Bundes Republik Deutschland Zusammenfassung. Die wesentlichen Aspekte der besonderen Bedeutung des Grundeigentums in der Bundesrepublik Deutschland werden zusammengestellt. Daraus werden die Aufgaben der öffentlich‐rechtlichen Bodenordnung in der Bundesrepublik Deutschland abgeleitet und das zugrundeliegende System der Bodennutzungsplanung erläutert. Schlußendlich werden für die Bundesrepublik Deutschland die wichtigen öffentlich‐rechtlichen Bodenordnungsinstrumente mit ihren privatnützigen und fremdnützigen Ausprägungen vorgestellt. Deskriptoren: Bodeneigentum, Bodenordmung, Bodennutzplanung. Žemės tvarkymas urbanizuotose Vokietijos Federacinės Respublikos teritorijose Santrauka. Straipsnyje apžvelgiami svarbiausi Vokietijos Federacinės Respublikos žemės nuosavybės aspektai. Nagrinėjami žemės nuosavybės įstatymai ir Konstitucijos nuostatai. Aprašoma valstybinio žemės tvarkymo bei jos naudojimo planavimo VFR sistemos esmė ir pagrindai. Pristatomi svarbiausi viešieji teisiniai žemės naudojimo pertvarkymo būdai iškilus naujiems miestų plėtros ir statybos, žemdirbystės bei gyvenviečių gerinimo, taip pat valstybės ir verslo poreikiams. Atsižvelgiama į asmeninius ir kitus interesus, keičiant sklypus bei jų ribas iki atlygintino žemės nusavinimo. Įvairiapusis žemės naudojimo planavimas VFR padeda išspręsti urbanizuotose teritorijose, ypač priemiesčiuose, iškylančias painias prieštaras ir išvengti planavimo bei investicijų klaidų. Pabrėžiama, kad efektyvus žemės tvarkymo priemonių taikymas yra susijęs su teisingu žemės įkainavimu. First published online: 03 Aug 2012